Fundamentals of organometallic electrophosphors synthesis under controlled temperature and ligand partial pressure. (February 2019) - Avetisov, Roman; Akkuzina, Alina; Kozlova, Natalya; Mozhevitina, Elena; Saifutyarov, Rasim; Avetissov, Igor
Abstract: A new technique for analysis of "Ligand partial pressure - Temperature" diagram has been developed for the organometallic phosphor tris(8-hydroxyquinoline) M (M = Al, Ga, In). The detection of mono- and bivariant equilibriums within the p 8-Hq - T diagram has been done using simultaneous measurements of photoluminescence and reflection spectra of a condense phase under controlled p 8-Hq and T . Using preparations with the purity better than 99.999 wt% the corresponding p 8-Hq - T diagrams have been plotted in the temperature range from 350 K to the maximum melting temperatures of the compounds. The homogeneity ranges of different polymorphs have been determined. For the different polymorphs it have been demonstrated that changing the synthesis conditions within the homogeneity range of the phases resulted to the significant changes of the nonstoichiometry, chemical activities and electroluminescent properties of the OLED structures, prepared on the base of β-Mq3 . Graphical abstract: Highlights: Technique for p ligand – T diagrams study of organometalic phosphors was developed. p 8-Hq – T diagrams of tris(8-hydroxyquinoline)indium was determined. Tris(8-hydroxyquinoline)gallium with controlled defect structure was examined.